2016
DOI: 10.1071/mf15300
|View full text |Cite
|
Sign up to set email alerts
|

Photobiology of the zoanthid Zoanthus sociatus in intertidal and subtidal habitats

Abstract: Intertidal environments are boundaries between marine and terrestrial ecosystems that are subject to rapid fluctuations across tidal cycles. This study investigates, for the first time, the photobiology of symbiotic zoanthids inhabiting different tidal environments: subtidal, intertidal pools and intertidal areas exposed to air during low tide. More specifically, we assessed the photochemical efficiency, Symbiodinium density and photosynthetic pigments profile of Zoanthus sociatus during low tide. Photochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, it has been demonstrated that size and weight greatly fluctuate in soft‐bodied organisms owing to their physiological state or in response to environmental disturbances (Fabricius, 1995; Hellström & Benzie, 2011). Moreover, previous studies have highlighted that photochemical efficiency in polyps that were cyclically emerged were lower than in polyps that were always immersed (Leal et al, 2015; Rosa et al, 2016). Nevertheless, under environmental stress the host can change its main feeding behaviour from autotrophy to heterotrophy (Gustafsson, Baird & Ralph, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been demonstrated that size and weight greatly fluctuate in soft‐bodied organisms owing to their physiological state or in response to environmental disturbances (Fabricius, 1995; Hellström & Benzie, 2011). Moreover, previous studies have highlighted that photochemical efficiency in polyps that were cyclically emerged were lower than in polyps that were always immersed (Leal et al, 2015; Rosa et al, 2016). Nevertheless, under environmental stress the host can change its main feeding behaviour from autotrophy to heterotrophy (Gustafsson, Baird & Ralph, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…However, the host can associate with at least three Symbiodiniaceae lineages that likely represent distinct species (Wham et al, 2014;Wham, 2015). Two of the lineages are primarily found in the shallows (Symbiodinium A1z in direct sunlight and Cladocopium C1z-intertidal in shadow; Reimer, 2008), while the other is primarily found at greater depth (Cladocopium C1z-subtidal), suggesting that they are adapted to different light levels and possibly different temperatures (Kamezaki et al, 2013;Leal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%